Physiology of Exercise and Healthy Aging - Taylor, Albert W.; Johnson, Michel J., 1966- (Leeds : Human Kinetics, 2008)
Taylor and Johnson blend the science of exercise physiology with the ageing process and identify the positive effects that regular exercise and physical activity have, not only on longevity, but also on delaying specific diseases.
Formerly CIP.
Includes bibliographical references (p. 235-261) and index.
Keywords: Aging -- Physiological aspects; Exercise -- Physiological aspects; Exercise for older people -- Physiological aspects; Aging -- physiology; Exercise -- physiology